(untitled) (Journal of International Crisis and Risk Communication Research, 2020)
Effective communication about medical countermeasures—including drugs, devices, and biologics—is often critical in emergency situations. Such communication, however, does not just happen. It must be planned and prepared for. One mechanism to develop communication strategies is through the use of prospective scenarios, which allow readers the opportunity to rehearse responses while also weighing the implications of their actions. This article describes the development of such a scenario: The SPARS Pandemic 2025–2028. Steps in this process included deciding on a time frame, identifying likely critical uncertainties, and then using this framework to construct a storyline covering both the response and recovery phases of a fictional emergency event. Lessons learned from the scenario development and how the scenario can be used to improve communication are also discussed.